Bitcoin sebagai Instrumen Investasi dalam Perspektif Keuangan Islam - Nurdiansyah, Irdan; Zaki Ibrahim, Hilmi (UIN Sunan Gunung Djati Bandung, 2025)
The rapid growth of financial technology has significantly increased interest in Bitcoin as an investment instrument, including among Muslim communities. However, its legal status in Islamic finance remains controversial due to its speculative nature and lack of underlying assets. This study aims to evaluate the compatibility of Bitcoin as a Sharia-compliant investment instrument by examining its status as māl (property), the potential presence of gharar (uncertainty) and maysir (speculation), and comparing it with established Islamic investment instruments. Using a qualitative approach and literature study method, the research analyzes fatwas, regulations, and relevant academic sources. The findings indicate that while Bitcoin is not yet fully aligned with Sharia principles, there is room for ijtihad to consider its use in investment—particularly if supported by stringent and transparent regulations. This study contributes to the discourse on Islamic digital finance by highlighting the need for developing Sharia-based cryptocurrencies backed by real assets. The conclusion emphasizes the urgency of establishing comprehensive regulations and enhancing Sharia digital literacy to mitigate risks and clarify legal standing for Muslim investors.